2022
DOI: 10.1016/j.ejso.2021.12.468
|View full text |Cite
|
Sign up to set email alerts
|

Human factors in pelvic surgery

Abstract: In the pelvis, anatomic complexity and difficulty in visualization and access make surgery a formidable task. Surgeons are prone to work-related musculoskeletal injuries from the frequently poor design and flow of their work environment. This is exacerbated by the strain of surgery in the pelvis. These injuries can result in alterations to a surgeons practice, inadvertent patient injury, and even early retirement. Human factors examines the relationships between the surgeon, their instruments and their environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The participant in this case study confirmed the claims of Symer and Keller (2022), indicating that rectal surgeries in which there is a need to access the surgical site via the pelvis causes more strain on the surgeon’s body compared to procedures performed abdominally. This is due to the requirement to work in asymmetric postures to access the pelvic region when using open or laparoscopic surgical techniques.…”
Section: Discussionsupporting
confidence: 60%
“…The participant in this case study confirmed the claims of Symer and Keller (2022), indicating that rectal surgeries in which there is a need to access the surgical site via the pelvis causes more strain on the surgeon’s body compared to procedures performed abdominally. This is due to the requirement to work in asymmetric postures to access the pelvic region when using open or laparoscopic surgical techniques.…”
Section: Discussionsupporting
confidence: 60%
“…Surgeons are at increased risk for WMSDs because of poor ergonomics from repetitive performance of static, extreme, and awkward positions for prolonged periods of time [3 && ]. Gynecologists face unique ergonomic challenges from operating in the pelvis, as it requires an oblique approach, which inherently inhibits appropriate ergonomics [4]. As minimally invasive surgery (MIS) has increasingly become the standard of care in gynecology, studies have shown high rates of associated surgeon discomfort during these procedures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gynecologists face unique ergonomic challenges from operating in the pelvis, as it requires an oblique approach, which inherently inhibits appropriate ergonomics [4]. As minimally invasive surgery (MIS) has increasingly become the standard of care in gynecology, studies have shown high rates of associated surgeon discomfort during these procedures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal is one subspecialty with particularly strong growth, as the robot's technology facilitates a high-definition view for meticulous dissection and greater flexibility maneuvering in the deep pelvis [3][4][5]. There are concerns that the growth of RAS outpaces the evidence to support its use and additional costs [2].…”
mentioning
confidence: 99%
“…Since 2012, utilization of robotic-assisted surgery (RAS) increased dramatically across all procedures, and certain operations shifted by an order of magnitude towards greater robotics use [ 2 ]. Colorectal is one subspecialty with particularly strong growth, as the robot’s technology facilitates a high-definition view for meticulous dissection and greater flexibility maneuvering in the deep pelvis [ 3 5 ]. There are concerns that the growth of RAS outpaces the evidence to support its use and additional costs [ 2 ].…”
mentioning
confidence: 99%